Membaca Teks Analitical Exposition Dengan Pendekatan Psikologi Kreativitas Sinektik - Djuharie, Otong Setiawan (JURNAL TARBAWIYAH, 2015)
This mini research entitled âReading Comprehension on Analitical Exposition Texts Through Sinectic Psychological Creativity, an Action Research in SMAN 24 Bandung Cityâ aims at describing learning reading through sinectic processes. This mini research describes (1) a sinectic model on reading comprehension, (2) hindrances in reading comprehension using sinectic model, (3) solutions to cope with such hindrances, and (4) the effectiveness of the sinectic model in reading comprehension.The findings show that first reading comprehension through the sinectic model constitutes certain strategies and steps, i.e., (1) opening (greeting, apperception, pretest), (2) sinectic activities (real input condition, direct analogy, direct analogy, personal analogy, comparative analogy, and contrastive analogy), (3) grouping students, assignements on comprehending texts, and analogical exercises (sinectic), (4) closing (post test and remarks).Second, there finds hindrances in applying sinectic model, i.e., (1) students are not accustomed to using analogy, (2) the teacher is not used to applying analogy in his/her teachings, (3) sinectic steps of exploring analogy and generating analogy are too difficult for the students.Third, solutions to such hindrances are (1) exposing students on using sinectic, (2) giving the teacher a guidance on how to apply sinectic, and (3) excluding the steps of exploring analogy and generating analogy.Fourth, sinectic model in reading comprehension is quite effective. The sinectic steps of nput condition, direct analogy, direct analogy, personal analogy, comparative analogy, and contrastive analogy can be used in various reading activities, especially in reading comprehension. Sinectic model can improve studentsâ comprehending texts. In adition, by using this model, students are able to express the contents of the readiing texts by way of making nanalogies of those contents through either input condition, direct analogy, direct analogy, personal analogy, comparative analogy, or contrastive analogy.